The Role of Brand Recall, Brand Recognition and Price Consciousness in Understanding Actual Purchase - Mehreen Khurram; Faisal Qadeer; Muhammad Sheeraz (Journal of Research in Social Sciences, 2018)
For making actual purchase in any category, the literature suggests that brand awareness plays a vital role. Whereas in existing literature the conceptual properties of brand awareness were less tapped in finding their impact on actual purchase. Therefore, the current study examined the impact of the two properties of brand awareness, i.e., brand recall and brand recognition on actual purchase of the consumers also testing the moderating effect of price consciousness in the relationship between brand recognition and actual purchase. Majority of the respondents for the study were female shoppers at the retail stores as they are the consumers as well as they play an active role in home budgets. Two separate studies were conducted, i.e., for brand recognition and brand recall, and the survey used 175 responses (125 for brand recognition and 50 for brand recall). The results revealed that brand recall and brand recognition have a positive relation to actual purchase. No moderating effect of price consciousness was found. The paper not only adds to the knowledge but is also important for managers in developing their strategies for the right fit between the brand recall and brand recognition being equally important for the actual purchase.
Keywords: 330; Brand Recall; Brand Recognition; Actual Purchase; Price Consciousness; Lawn Brands; Pakistan